Strain-induced modifications of the band structure of InxGa1-xP–In0.5Al0.5P multiple quantum wells - Fouquet, Julie Elizabeth, author; Thiagarajan, Prabhuram, author; Robinson, Gary Y., author; Menoni, Carmen S., author; Patel, Dineshchandra, author; Interholzinger, Kathryn, author; IEEE, publisher (Colorado State University. Libraries, 1998)
The effect of strain on the band structure of InxGa1-xP-In0.5Al0.5P multiple quantum wells (MQW's) has been investigated from high-pressure and low-temperature photoluminescence measurements. The biaxial strain in the wells was varied between +0.6% compressive to -0.85% tensile strain by changing the well composition x from 0.57 to 0.37. Strain increases the valence band offsets in either tensile or compressively strained structures. Whereas relatively insensitive to tensile strain, the valence band offsets showed a strong dependence on the magnitude of the compressive strain. Good agreement is found between the measured valence band offsets and those predicted by the model solid theory, except for the largest compressively strained MQW's, for which the model calculations underestimate the measured valence band offset. Strain and the associated variations in composition also modified the separation among the well states associated with Γ1c, L1c, and X1c. From these results, the bandgaps of each conduction band extrema were calculated in InxGa1-xP for 0.37 < x < 0.57 and compared with the predictions of the model solid theory.
Keywords: quantum wells; strain; heterojunctions; photoluminescent materials/devices; pressure measurements; semiconductor heterojunctions